Magnetic properties optimization of novel composite magnetic materials for HSPMSM with novel composite rotor - Jinyu Yao; Huijun Wang; Yue Zhang; Deming Xiong; Fengge Zhang (Energy Reports, 2022)
The key problems of HSPMSM have also extensive attention, which are stress concentration and high temperature rise. The new rotor topology of HSPMSM is proposed. The main components of novel composite rotor are novel composite magnetic materials(NCMM), which are made by carbon fiber and magnetic powder film. The no-load and load performance of NCR-HSPMSM is significantly affected by change the structure of NCMM. To optimize the magnetic properties of NCMM, the surrogate model of the magnetic powder mixing of various sizes is proposed for NCMM. And on the basis of the surrogate model, the NCMM are optimized by the optimization algorithm. Considering the optimized magnetic materials, the effect of the NCR-HSPMSM on the electromagnetic performance are analyzed.